Genome-wide DNA demethylation in mammals - Sanz, Lionel A (BioMed Central, 2010)
The cytidine deaminase AID and elongator-complex proteins contribute to the extensive removal of DNA methylation in mammalian primordial germ cells and in the paternal pronucleus of the zygote.